Adolescent Mothers' Perceptions of a Mobile Phone-Based Peer Support Intervention. Issue 2 (June 2020) - Chyzzy, Barbara; Nelson, LaRon E.; Stinson, Jennifer; Vigod, Simone; Dennis, Cindy-Lee
Background: Postpartum depression (PPD) is prevalent among adolescent mothers and is associated with negative maternal and infant outcomes. Peer support can improve health outcomes among adult and adolescent populations and involves the provision of informational, emotional, and appraisal support delivered by a peer. Purpose: To describe adolescent mothers' perceptions of a mobile phone-based peer support (MPPS) intervention designed to prevent PPD. Methods: This analysis draws on data from the MPPS intervention group of a pilot randomized controlled trial of pregnant adolescents 17 to 24 years old ( n  = 16). Maternal perceptions of the intervention were measured using the validated Peer Support Evaluation Inventory at 12 weeks postpartum. Results: Participants acknowledged receiving supportive actions including emotional (91%), informational (66%), and appraisal (64%) support. Participants perceived positive relationship qualities with their peer mentor such as trustworthiness (94%), acceptance (75%), empathy (81%), and commitment (81%) and felt their peer mentor possessed social competence (91%) and social skills (91%). Overall, 100% of participants were satisfied with their peer support experience and would recommend this type of support to a friend. Conclusion: Participants perceived their experience with the MPPS intervention positively, which lends support to MPPS as an acceptable way to provide support to adolescent mothers.